Infringement, sanction and other legal institutions of administrative law not necessarily related to the sanctioner - Huamán Ordóñez, Luis Alberto (2020)
The author analyzes the issue of administrative infraction as an institute close to the notion of punishment, since it handles the notion of typicity, unlawfulness and guilt, although in an attenuated scenario where the administration is unable to determine punishments that involve deprivation of liberty of the person who interacts as administered also focusing on the institute of the sanction with the purpose of understanding the reasons why it is conceived as an evil what would seem to move from a mannequin view of the good and the bad that is contrary to the vicarial vision of the administration tied to the objectivity of public action; in the same way, it focuses on certain institutions adjacent to the sanctioning Law such as the measures to restore the legality, the administrative orders for the cessation of activities, the warnings, intimations and requirements, the suspension with the order of reimbursement of economic benefits to the administration, the institute of the expiration of administrative concessions, the suspension or loss of ability for payment of fees, seizures and measures of bodily intervention, the vehicular withdrawal of the National Land Transportation System, compensation to the administration for damages generated by the particular as well as the pass to retirement for renewal of cadres in the military and police field next to the administrative control that they run in the sanctioning scenario without being properly administrative sanctions.